Strategi Fadil Jaidi dalam Meningkatkan Visibilitas Produk melalui Endorsement dan Teknik Pemasaran terhadap Followersnya - Destiny Priscillia Tandean; Gearen Wahyudi; Joseline Yap; Rayshella Angelina Djifri; Rahmi Yulia Ningsih (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
This research aims to determine Fadil Jaidi's strategy in increasing product visibility through endorsements and marketing techniques for his followers at Bina Nusantara University. The research method used is quantitative with data collection techniques through questionnaires. The research results show that Fadil Jaidi uses various innovative and authentic endorsement strategies, as well as effective marketing techniques to attract attention and increase audience interest in the products he endorses. This endorsement strategy and marketing technique has proven effective in increasing product sales, but further efforts are still needed to increase purchase conversions. The influence of the number and involvement of followers, especially Bina Nusantara University students, plays an important role in the success of Fadil Jaidi's marketing campaign. Fadil Jaidi faces several challenges and obstacles in his efforts to increase product visibility, such as the low frequency of active interaction from followers and the lack of efficient cross-platform promotion.